P-T conditions of metamorphism inferred from the metabasites of the Cape Smith Belt, northern Quebec - Begin, N. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1989)
Summary In the Cape Smith Belt, lower green schistto middle-amphibolite facies metabasites are exposed in an oblique cross-section displaying over 18 km of structural relief. Mapping of regional mineral isograds has documented the nature and relative timing of the thermal responses to southward directed crustal thickening. In the belt's foreland, hot-side-down metamorphism followed a stage of regular-sequence thrusting. Syn-thermal peak out-of-sequence thrusting was reponsible for local inversion of the isograds in the foot wall of the out-of-sequence domain. In the belt's hinterland, post-thermal peak out-of-sequence faulting produced pervasive retrogression to green schist facies and truncation of the thermal peak isograds.